A Multi-sensory Approach to the Teaching of English as a Second Language through the Use of Dramatic Activities - Souza, Bernadette D' (JOURNAL OF INDIAN EDUCATION, 2011)
A boring English Language class can be transformed into an exciting experience, through the inclusion of dramatic activities for all age groups and all levels of schooling. These activities have an amazing and tremendous effect on students as they touch upon multi-learning styles and intelligences through a multi-sensory approach.Children have a natural desire to ‘act’ or to ‘express’ their inner feelings in some outward form, and so, with the introduction of dramatic activities into classroom teaching, they are provided with the necessary outlet for their feelings and emotions. From an early age they create characters and stories to explore the world around them. The non-verbal communicative aspects of language like body language, gestures, and facial expressions, as well as verbal aspects – voice-modulation, intonation, rhythm, stress, and idiomatic expressions, are drawn out in a natural manner.Everything depends on the creativity and enthusiasm of the language teacher. As Albert Einstein had stated, “It is the supreme art of the teacher to awaken joy in creative expression and knowledge”. This can be achieved by various dramatic activities for students who are nonnative speakers of English!